Genetic polymorphism of modern common flax (Linum usitatissimum L.) cultivars developed at Russian breeding centers using SSR markers - T. A. Bazanov; I. V. Ushchapovskii; V. A. Lemesh; M. V. Bahdanava; A. V. Lahunovskaya (Труды по прикладной ботанике, генетике и селекции)
Background. Molecular identification of plant genomes, based on the use of DNA markers, is becoming a reliable tool for cultivar identification. Widespread application of DNA markers will ensure protection of breeders’ rights for plant breeding centers, purity of seed production processes, and transparency of the domestic crop seed market. The system of SSR markers is suitable to solve the problems of identification and genetic profiling of many crops; it could be successfully used on flax and linseed. The aim of this work was to study the polymorphism of a number of modern Russian common flax cultivars and develop their genetic profiles.Materials and methods. Among the large number of SSR markers (over 1300) used for common flax (Linum usitatissimum L.), the most informative for genotype identification is, in our opinion, the set of 11 SSR primers, characterized by their highest precision. This set of markers was used to study the polymorphism of eleven flax cultivars developed in three geographically diverse locations – Tver, Pskov and Tomsk.Results and discussion. In the studied group of cultivars 53 alleles were identified: 15 of these appeared to be rare, including 11 unique ones. Each flax sample contained its specific set of alleles. Using the alphabetic code for SSR markers made it possible to develop genetic profiles for more precise genotyping of flax samples hardly distinguishable morphologically, thus providing an opportunity to effectuate genetic profiling for all flax cultivars listed in the State Register of Breeding Achievements in Russia. Cluster analysis with a dendrogram showing genetic similarities helped to find differences among the studied flax samples in their distribution according to the place of their origination and the duration of their growing seasons.